The impossible rescue - Sandler, Martin W. (Candlewick Press, 2012)
In 1897, whaling in the Arctic waters off Alaska's coast was as dangerous as it was lucrative. And in that particular year, winter blasted early, bringing storms and ice packs that caught eight American whale ships and three hundred sailors off guard. Their ships locked in ice, with no means of escape, the whalers had limited provisions on board, and little hope of surviving until warmer temperatures arrived many months later. Here is the incredible story of three men sent by President McKinley to rescue them. The mission? A perilous trek over 1,500 miles of nearly impassable Alaskan terrain, in the bone-chilling months of winter, to secure two herds of reindeer (for food) and find a way to guide them to the whalers before they starve. With the help of photographs and journal entries by one of the rescuers, Martin W. Sandler takes us on every step of their riveting journey, facing raging blizzards, killing cold, injured sled dogs, and setbacks to test the strongest of wills.